Clinical and functional profile of 6-12-year-old children with attention deficit hyperactivity disorder referred to a tertiary care center in South India - Dr. Arpita Gupta; Dr. Babu George; Dr. MKC Nair; Dr. Leena ML; Dr. Deepa Bhaskaran (International Journal of Medical Research and Review, 2020)
Objective: To describe the clinical, socio-demographic, and functional profile of children with Attention Deficit Hyperactivity Disorder (ADHD) referred to a tertiary care center in Kerala, India. Methods: A retrospective descriptive study was conducted from records of developmental evaluation clinic over a period of one year. All-consecutive cases the first time diagnosed as ADHD were enrolled. Autism Spectrum Disorder, genetic disorders, and children with sensory impairments were excluded. Clinical profile was based on presenting symptoms, gender, and socio-demographic characteristics; functional status assessed by Conner’s 3 Parent Scale and cognitive status by Intelligence Quotient. Results: ADHD prevalence in a clinically referred sample was 12.7%. Boy to girl ratio was 6:1. The mean age of presentation was 8.2 years (SD 6.09). The most common presenting symptom was hyperactivity and behavioral problems followed by poor scholastic performance and poor memory. The functional status assessment showed major concerns in all six domains - Inattention, Hyperactivity, Learning Problem, Executive Functioning, Aggression, and Peer relation, in the majority of children. Children presenting with ADHD symptoms at a later age (9-12 years) had lower IQ scores than those diagnosed at a younger age. Conclusion: Course of childhood ADHD shows a consistent clinical and functional pattern. Early diagnosis and quantification of difficulties at the outset is suggested, which can help in providing early intervention and is likely to improve long-term outcome in these children.